COMMITMENT-BASED CAPITATION EVALUATION IN BENGKULU PROVINCE: A REALIST EVALUATION - Susilo Wulan; S Effendi; Dirhan Dirhan; Chandrainy Puri; Hanevi Djasri (Poltekkes Kemenkes Bengkulu, 2022)
Primary Health Care (FKTP) as the gate keeper of health service providers must have a strategy in improving service quality and patient satisfaction. This study aims to evaluate the implementation of regulations regarding commitment-based capitation policies and determine the mechanism of change and contextual factors that affect the implementation of regulations. The evaluation was carried out using a realist evaluation approach and analyzed in terms of the configuration of forms, mechanisms, and results. The research was carried out in Bengkulu Province in 2018-2019 with the research subjects consisting of the health office, the head of the Puskesmas and the JKN monev team, Private Practice Doctors, Pratama Clinics. The sample selection used purposive sampling and data collection was carried out through in-depth interviews. Commitment-Based Capitation (KBK) is running in Bengkulu province. The KBK program shows that in general the non-specialist referral indicator target in Bengkulu province is achieved, namely 5%, but there are also city districts that have not been achieved, this is achieved because the Puskesmas has doctors in Bengkulu province, adequate doctor competence, adequate facilities and infrastructure, staff receive capitation funds incentives, there is a JKN Monev team that is always active in conducting socialization, monitoring and evaluation in all Puskesmas, especially Puskesmas that do not achieve non-specialist referral indicators. This study provides an overview of the context, mechanism and outcome of health service quality policy regulations in the JKN era, especially the Commitment-Based Capitation program.